2019
DOI: 10.1109/tit.2019.2905002
|View full text |Cite
|
Sign up to set email alerts
|

New LMRD Code Bounds for Constant Dimension Codes and Improved Constructions

Abstract: We generalize upper bounds for constant dimension codes containing a lifted maximum rank distance code first studied by Etzion and Silberstein. The proof allows to construct several improved codes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…If a CDC contains an LMRD, see Section II for the definition, then the best known upper bound on the cardinality for the general case can be improved. Corresponding results have been obtained in [2], [4] for a restricted range of parameters. Here we remove the restriction and generalize those bounds to all parameters.…”
Section: Ksupporting
confidence: 63%
See 1 more Smart Citation
“…If a CDC contains an LMRD, see Section II for the definition, then the best known upper bound on the cardinality for the general case can be improved. Corresponding results have been obtained in [2], [4] for a restricted range of parameters. Here we remove the restriction and generalize those bounds to all parameters.…”
Section: Ksupporting
confidence: 63%
“…For some special cases, Etzion and Silberstein have demonstrated that one can obtain tighter upper bounds on the maximum possible cardinality of CDCs if we assume that an LMRD code is contained [2]. The range of applicable parameters was partially extended by Heinlein in [4]. Here we fully generalize those bounds, which also sheds some light on recent constructions.…”
Section: Generalized Lmrd Code Bounds For Constant Dimension Codesmentioning
confidence: 72%
“…Lifted MRD codes can often be extended to larger subspace codes, but again not always to optimal subspace codes. Some recent results on this can be found in [15], [44], with further background and open problems in [32].…”
Section: Subspace Codesmentioning
confidence: 99%
“…and we can calculate that rank V V A l = 5 or 6, for any l ∈ {0, 1, • • • , 62}. Using (2), we get Therefore, C(3, 0, 6) is an (6,63,4,3) unitary cyclic orbit code.…”
Section: Constructions Of Cyclic Orbit Codes Base On Totally Isotropic Subspaces In Unitary Spacementioning
confidence: 99%
“…Xu and Chen [3] presented an effective construction which can be seen as a generalization of the lifted maximum rank distance codes. Heinlein [4] generalized the upper bounds of for constant dimension codes which contain lifted maximum rank distance codes. In [5], Luerssen et al proposed a new construction coming from Corollary 39 in [6] which was named as the linkage construction.…”
Section: Introductionmentioning
confidence: 99%